Representing Recovery: How the Construction and Contestation of Needs and Priorities Can Shape Long-term Outcomes for Disaster-affected People. (January 2021) - Few, Roger; Marsh, Hazel; Jain, Garima; Singh, Chandni; Tebboth, Mark Glyn Llewellyn
We contend that the representational aspects of recovery play an important but under-researched role in shaping long-term outcomes for disaster-affected populations. Ideas constructed around events, people and processes, and conveyed through discussion, texts and images, are seldom neutral and can be exclusionary in their effect. This review draws insights from literature across multiple disciplines to examine how the representation of needs, roles and approaches to recovery influences the support different social groups receive, their capacities to recover, and their rights and agency. It shows how these representations can be contested and challenged, often by disaster-affected people themselves, and calls for increased attention on how to move creatively towards more informed, inclusive and supportive recovery visions and processes.